5% Imiquimod Cream으로 치료한 눈썹부위 바닥세포암 증례 1예 - 강병수(Byeong Soo Kang), 김남주(Nam Ju Kim), 정호경(Ho Kyung Choung), 곽상인(Sang In Khwarg) (Daihan angwa haghoi jabji, 2015)
목적: 바닥세포암은 가장 흔한 피부악성종양으로 눈 주변부에 발생하는 경우 미용적인 관점과 안와 내로의 침범 예방을 위하여 치료가 필요하다. 이에 대한 치료 중 면역반응조절제인 imiquimod 연고를 통한 비수술적 치료의 효과가 보고되어 왔다. 눈 주변의 바닥세포암에 대한 imiquimod 국소요법의 증례가 국내 안과 관련 학회지에서는 보고된 바가 없어 이에 대한 증례 1예를 보고하고자 한다. 증례요약: 73세 여자 환자가 서서히 커지는 우측 눈썹의 종양으로 시행한 조직검사상, 바닥세포암으로 진단 받고 서울대학교병원에방문했다. 내원 시 우측 눈썹의 중앙부 안쪽에 편평하게 융기되고 중심부는 경도로 함몰된 양상의 1x1 cm 크기의 종양이 관찰되었다. 5% Imiquimod 연고를 1주에 5일 동안 수면 시간에 우측 눈썹 종양 부위에 6주간 바르도록 하였다. 이후 8주가 지났을 때 종괴는호전된 양상이었으나 완전 관해로 판단되지 않아 추가로 4주간 투여하였고, 점점 정상 피부 모습으로 변하였으며, 최종 추적관찰한31개월 후에는 정상 눈썹 피부 모습이 관찰되었다. 결론: Imiquimod 연고는 종양의 수술적 제거 후 재건이 어렵거나 수술이 어려운 경우 유용하게 시도될 수 있는 치료제로 생각한다. Purpose: Basal cell carcinoma is the most common malignant neoplasm of the skin. Periorbital basal cell carcinoma needs to be treated for cosmetic improvement and prevention of intraorbital invasion. Although surgical excision is a standard treatment, nonsurgical treatment using imiquimod cream, a topical immunomodulator, has been attempted. The authors report the first case of periorbital basal cell carcinoma successfully treated with imiquimod cream; to the best of our knowledge, similar cases have not been published to date in the Korean ophthalmology journals. Case summary: A 73-year-old female visited our hospital for treatment of a biopsy-proven basal cell carcinoma in the right eyebrow. A flat, elevated, 1 x 1 cm-sized mass having central indentation was observed in the centromedial area of the right eyebrow. She was treated with 5% imiquimod cream once daily at night, 5 days per week for 6 weeks. Eight weeks after the treatment with imiquimod cream was discontinued, the mass was flattened and the cilia began to grow on the mass site. Under the impression of a partial regression, an additional 4 weeks of application was recommended. The mass disappeared more and her eyebrow became more normal. At the final follow-up 31 months after treatment, her right eyebrow appeared normal. Conclusions: Imiquimod cream may be a useful medication which can be used for complex periorbital basal cell carcinomas that are difficult to reconstruct after resection or surgical candidates with poor general condition. KCI Citation Count: 0